La interpretación schmittiana de Hobbes - Sirczuk, Matías (Foro Interno, 2007)
This paper focuses on Carl Schmitt’s interpretation of Thomas Hobbes. We will argue that, for Carl Schmitt, the first modern answer to the problem of the absence of a transcendent foundation for the political order was to be found in Hobbes’ theory. In two phases, we examine the tension that Schmitt finds in the Hobbesian solution to the problem of truth in politics. First, we present some problems that Schmitt encountered in Hobbes’ solution, focusing on Schmitt’s interpretation of the Hobbesian distinction between inner faith and outer confession. Second, we outline some difficulties that arise from Schmitt’s interpretation of this problem.